2011
DOI: 10.1097/ico.0b013e3181eadeb9
|View full text |Cite
|
Sign up to set email alerts
|

Severe Arthrographis kalrae Keratomycosis in an Immunocompetent Patient

Abstract: Ocular infection with A. kalrae is very rare. The microbiological differentiation of A. kalrae can be difficult. Because a broad spectrum of fungi is sensitive to voriconazole, the early topical and possibly systemic treatment is a reasonable therapeutic option when a mycotic infection of the eye is suspected, even before the causative fungus is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
1
10
0
6
Order By: Relevance
“…Most A. kalrae keratitis reports showed successful treatment with amphotericin B, itraconazole, ketoconazole and voriconazole; our patient however only undergone suboptimal medical treatment which showed positive responds initially [1012]. His condition however deteriorated since he discontinued treatment, besides poor host defense mechanism due to underlying uncontrolled diabetic mellitus.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Most A. kalrae keratitis reports showed successful treatment with amphotericin B, itraconazole, ketoconazole and voriconazole; our patient however only undergone suboptimal medical treatment which showed positive responds initially [1012]. His condition however deteriorated since he discontinued treatment, besides poor host defense mechanism due to underlying uncontrolled diabetic mellitus.…”
Section: Discussionmentioning
confidence: 79%
“…There are three reports on A. kalrae keratitis, and all cases showed that it is frequently implicated by ocular trauma by foreign body inoculation besides all cases are associated with contact lenses. The clinical presentations were similar to Acanthamoeba keratitis with history of photophobia [312]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed high MICs for AMB, and, although our results showed good in vitro activity for the azoles, the results are variable in the clinical setting. VRC and ITC have been the most commonly used drugs against A. kalrae infections, although mostly with negative results even when high doses were employed . In contrast, a mycetoma case was successfully treated using long‐term ITC therapy, whereas a case of panophthalmitis and invasive sinusitis required a combination of ITC, fluconazole and a drastic surgical debridement .…”
Section: Resultsmentioning
confidence: 99%
“…VRC and ITC have been the most commonly used drugs against A. kalrae infections, although mostly with negative results even when high doses were employed. 7,9 In contrast, a mycetoma case was successfully treated using long-term ITC therapy, 3 whereas a case of panophthalmitis and invasive sinusitis required a combination of ITC, fluconazole and a drastic surgical debridement. 5 There are no reports on the use of echinocandins against A. kalrae infections and we observed high rates of in vitro resistance to these drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, one case of infection with Arthrographis sp. and 14 cases of infection with A. kalrae have been reported (Table 1): two onychomycosis [2], [3], one mycetoma [4], five keratitis [5], [6], [7], [8], [9] one of which associated with sinusitis [8], two knee joint infection [10], [11], one endocarditis [12], two pulmonary infections [13], [14], one meningitis [15] and one fungal stroke [16]. These cases have a worldwide distribution: seven cases in Europe, one in China, one in Japan, three in USA, one in Mexico, one in Malaysia and one in Australia.…”
Section: Discussionmentioning
confidence: 99%